ANALYSIS ON THE SPATIAL CORRELATION BETWEEN LAND COVER AND THICKNESS OF LATERITIC NICKEL ZONES AT GEE AND PAKAL ISLANDS, EAST HALMAHERA, NORTH MALUKU PROVINCE - MUHAMMAD INDRAGIRI (NIM : 22107017), NOOR
Remote sensing is an indirect method of analyzing aerial photographs or satellite images. This study aims to analyze the spatial correlation between land cover and the thickness of the nickel laterite Gee and Pakal island. Satellite imagery is used Landsat TM and ASTER. In this study used the assumption that genesa of nickel laterite deposits are in addition affected by weathering processes are also influenced by vegetation. Parameters used in analyzing land cover include FCD (Forest Canopy Density), Savi (Soil adjusted vegetation index) and MSAVI (Modified soil adjusted vegetation index). The data used is the thickness, levels of Ni, Fe and Mg levels on Top Soil and Total laterite. FCD values, Savi and MSAVI are overlay with estimated value of the thickness and amount of each nickel laterite morphology of each type to see the spatial correlation . Regional Research and Pakal Gee Island has a density value of the land cover of vegetation canopies (FCD) with a range of values from 2.5 to 98.5 and SAVI value range from -0.27 to 0.66, and values range from MSAVI - 0.01 to 0.92 It could be concluded in this study that the method of FCD having correlation coefficient values tend to be constant and nearly equal to the line parameters and total laterite soil in the direction toward the steep sloping morphology compared SAVI methods and MSAVI